Trends in The Implementation of Digital Teaching Materials Based on Local Wisdom in The Modern Education System - Sri Aliyah; Cici Madiyawati; Mirna Wahdaniyati (Indonesian Publication Center, 2024)
The development of digital technology has been a major driver of significant changes in education, particularly in the creation of technology-based instructional materials. In today’s educational setting, it is important to integrate local wisdom into digital instructional materials to preserve cultural identity and enhance the relevance of the learning process. The purpose of this study is to examine the development of the application of digital instructional materials based on local wisdom through a literature review. This study employs a qualitative approach by conducting a literature review of 25 scientific articles published between 2015 and 2023. The selection process involved identification, screening, eligibility assessment, and inclusion steps adapted from the PRISMA principles. Data analysis was conducted using content analysis techniques, including coding, grouping, and synthesis of findings. The research findings indicate that digital teaching materials based on local wisdom can enhance students’ motivation to learn, deepen their understanding of concepts within a contextual framework, and contribute to the development of students’ character. However, current research remains dominated by descriptive approaches and lacks support from structured development models.